Study of Sequence of Histopathological Changes in Hyperglycaemia-Induced Experimental Diabetic Nephropathy in Wistar Rat Model - Elum, Fischer Christie Elum; Abang, Agbor Cyril Abang; Ezeteonu, Abireh Ifeanacho Ezeteonu; Agim, Agaba Eric Agim (Journal of Bio-Science, 2023)
The sequence of histopathological changes in hyperglycaemia-induced nephrotoxicity as well as alteration in renal parameters is still not well established in diabetic models. Hyperglycaemic ambience has been shown to generate oxidative stress which becomes a trigger for further degenerative changes that occur in the microenvironment of the kidney. This study was therefore intended to investigate histopathological alterations in vascular, glomerular and tubulointerstitial compartments of the renal tissues, and the corresponding changes in values of oxidative stress markers, creatinine clearance, proteinuria and serum creatinine concentration in a duration of three, seven and twelve weeks of sustained hyperglycaemia in diabetic. The experiment included four groups of adult Wistar rat, Group A (Normal Control, treated with normal saline), Groups B, C and D were induced with diabetes (treated with 65mg/kg body weight of streptozotocin) and allowed for 3 weeks 7 weeks and 12 weeks respectively. At termination, Oxidative stress markers were analyzed using Oxidative stress marker kits. A 24 hours urine collection was obtained from metabolic cages few hours before sacrifice and used for renal analysis and histopathological examination was done using a light microscope. Results reveals that oxidative stress was climaxed at 7th week and was maintained at a constant level while histopathological changes in glomerulus first presented on the 3rd week accompanied by vascular changes. Tubulointerstitial changes were noticed on the 7th week. On the 12th week renal parameters were significantly altered when compared to the animals sacrificed on 3th and 7th week. In conclusion, the sequence in diabetic–induced renal dysfunction begins with changes in vascular and glomerular compartment followed by distortion in tubulointerstitial compartment. An alteration in renal parameters presents lastly and correlates with the histopathological changes. These findings can be adopted in clinical management and treatment of diabetes-induced kidney dysfunction. J. Bio-Sci. 31(1): 29-37, 2023